Factors associated with (non-)participation of cancer survivors with job loss in a supportive return to work program - van Egmond, Martine P. (Support Care Cancer, 2016)
PURPOSE: To evaluate and implement supportive programs, it is important to understand which cancer survivors (CSs) are participating in these programs and which motives exist for declining participation. Recently, a supportive return-to-work (RTW) program was offered to CSs with job loss. The purpose of this study was to identify factors and motives associated with (non-)participation of CSs with job loss in the RTW program. METHODS: In this cross-sectional study (N = 286), information on socio-demographic, health-related, psychosocial, and work-related characteristics of CSs in the program was collected. Similar data were collected from those who declined participation. Multivariable logistic regression analyses were conducted (p < 0.05) to identify factors associated with (non-)participation. Motives for declining participation were identified using descriptive analysis. RESULTS: Being married (odds ratio (OR) 0.23; 95 % confidence interval (CI) 0.08–0.69) or living together (OR 0.25; 95 % CI 0.07–0.96) decreased the likelihood of participation in the RTW program. Having a temporary employment contract prior to unemployment (OR 2.60; 95 % CI 1.20–5.63), a clear intention to RTW (OR 2.65; 95 % CI 1.20–5.82), and higher scores on a readiness to RTW instrument, i.e., contemplation scale (OR 2.00; 95 % CI 1.65–2.40) and prepared for action–self-evaluative scale (OR 1.27; 95 % CI 1.04–1.54), increased the likelihood of participation. Physical (50 %) and mental problems (36 %) were leading motives for declining participation. CONCLUSIONS: The results from this study help to distinguish CSs that may not need RTW support, from those who are most in need of RTW support. Practitioners and researchers should tailor RTW support to CSs’ socio-demographic, health-related, and work-related characteristics.